Influence of Packaging on Consumer Purchasing Behavior - Zakharova, Kateryna; Král, Petr, 1979-; Bockstefel, Jan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The usage of the packaging as the marketing tool gains on its importance and allows companies to differentiate from each other and gain the attention of the potential customer. The aim of the current thesis is to provide an analysis of the impact of packaging on the consumer buying behavior on the example of the chosen company. Moreover, the research investigated to which extent company's customers are satisfied with the packaging they get, and to which extent such packaging incited them to buy the chosen company's products. Furthermore, the recommendations regarding packaging were presented. The mixed research method has been chosen for the research, since it provided a complex picture on the researched area, it included both quantitative and qualitative approaches. The data collection included the qualitative research in the form of the interview with the manager of the chosen company and quantitative research which was conducted and analyzed through the survey.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses